The smell of time in Ana Margarida de Carvalho’s Não se pode morar nos olhos de um gato: an outline of the human condition - Gago, Dora Nunes (Acta Scientiarum. Language and Culture, 2021)
This article analyses the olfactory landscapes represented in the novel Não se pode morar nos olhos de um gato (You can’t live in a cat’s eyes) by Ana Margarida de Carvalho (2016) reflecting upon the way in which the various smells described ‘presentify’ the multiple memories of the characters, emphasising their human dimension in a confinement scenario predisposed to completely dehumanising them. Using the theoretical contributions of Drobnick (2006a, 2006b), Reinarz (2014) and Byung-Chul Han (2015) among others, we examine how the smellscapes contribute to the construction of the characters’ identitary memory giving the narrative temporal cohesion.